Arterial load and right ventricular-vascular coupling in pulmonary hypertension - Oakland, Hannah (J Appl Physiol (1985), 2021)
Right ventricular (RV) functional adaptation to afterload determines outcome in pulmonary hypertension (PH). RV afterload is determined by the dynamic interaction between pulmonary vascular resistance (PVR), characteristic impedance (Z(c)), and wave reflection. Pulmonary vascular impedance (PVZ) represents the most comprehensive measure of RV afterload; however, there is an unmet need for an easier bedside measurement of this complex variable. Although a recent study showed that Z(c) and wave reflection can be estimated from RV pressure waveform analysis and cardiac output, this has not been validated. Estimations of Z(c) and wave reflection coefficient (λ) were validated relative to conventional spectral analysis in an animal model. Z(c), λ, and the single-beat ratio of end-systolic to arterial elastance (E(es)/E(a)) to estimate RV-pulmonary arterial (PA) coupling were determined from right heart catheterization (RHC) data. The study included 30 pulmonary artery hypertension (PAH) and 40 heart failure with preserved ejection fraction (HFpEF) patients [20 combined pre- and postcapillary PH (Cpc-PH) and 20 isolated postcapillary PH, (Ipc-PH)]. Also included were 10 age- and sex-matched controls. There was good agreement with minimal bias between estimated and spectral analysis-derived Z(c) and λ. Z(c) in PAH and Cpc-PH groups exceeded that in the Ipc-PH group and controls. λ was increased in Ipc-PH (0.84 ± 0.02), Cpc-PH (0.87 ± 0.05), and PAH groups (0.85 ± 0.04) compared with controls (0.79 ± 0.03); all P values were <0.05. λ was the only afterload parameter associated with RV-PA coupling in PAH. In the PH-HFpEF group, RV-PA uncoupling was independent of RV afterload. Our findings indicate that Z(c) and λ derived from an RV pressure curve can be used to improve estimation of RV afterload. λ is the only afterload measure associated with RV-PA uncoupling in PAH, whereas RV-PA uncoupling in PH-HFpEF appears to be independent of afterload consistent with an inherent abnormality of the RV myocardium. NEW & NOTEWORTHY Pulmonary vascular impedance (PVZ) represents the most comprehensive measure of right ventricle (RV) afterload; however, measurement of this variable is complex. We demonstrate that characteristic impedance (Z(c)) and a wave reflection coefficient, λ, can be derived from RV pressure waveform analysis. In addition, RV dysfunction in left heart disease is independent of its afterload. The current study provides a platform for future studies to examine the pharmacotherapeutic effects and prognosis of different measures of RV afterload.